Pro-elderly welfare states within pro-child societies: Incorporating family cash and time into intergenerational transfers analysis. - Rob́ert Ivań Gaĺ; Pieter Vanhuysse; Lili Vargha (Hungarian Demographic Research Institute, 2016)
Households and welfare states both serve as vehicles of lifecycle financing through~intergenerational transfers. Working-age people are net contributors, children and the~elderly are net beneficiaries. However, there is a marked asymmetry in the socialization~of intergenerational transfers. Working-age people pay taxes and social security~contributions to care for the elderly as a generation, but they individually spend cash~and contribute time to raise their own children. This results in asymmetric visibility of~intergenerational transfers. Resources flowing to the elderly are near-fully observed~in National Accounts (NA), but inter- and intra-household transfers are not registered~there. Using data for ten European countries representing 70% of the population of~the EU, we employ National Transfer Accounts (NTA) to include private transfers as~well. In addition, as an extension of NTA, we use National Time Transfer Accounts~(NTTA) to quantify the value of time transferred within and between households in~the form of unpaid labor. Only a fifth of all resource transfers to children is registered~in NA; another third is made visible by NTA, but nearly half is made visible only by~NTTA. Contrary to much perceived wisdom, once intra-familial transfers of cash and~time are incorporated, European societies transfer more resources to children than~to the elderly.
Keywords: D14; 300; household economy; young and old; care work; child rearing; families; National Transfer Accounts; Öffentliche Sozialleistungen; Generationengerechtigkeit; Familienleistungsausgleich; Sozialstaat; Volkswirtschaftliche Gesamtrechnung; EU-Staaten